2013
DOI: 10.1111/cen.12234
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin measurement in aspiration needle washout fluids has higher sensitivity than cytology in detecting medullary thyroid cancer: a retrospective multicentre study

Abstract: This study shows, as the first in a multicentre series, that FNA-CT sensitivity is higher than that of cytology in diagnosing MTC. To avoid false-negative MTC by cytology, CT measurement in aspiration needle washout is to be performed in all patients undergoing biopsy following high serum CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
75
2
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(91 citation statements)
references
References 25 publications
4
75
2
10
Order By: Relevance
“…The procedure may also be required in cases where serum CEA is elevated and the primary cancer is unknown [3]. The specificity and sensitivity of wash-out fluid examination are higher than those of FNAC [6,7,11]. In our study, the sensitivity was higher (96.3%) than that of FNAC (76.5%); however, false positives may occur owing to peripheral blood contamination in patients with extremely high serum calcitonin [11].…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…The procedure may also be required in cases where serum CEA is elevated and the primary cancer is unknown [3]. The specificity and sensitivity of wash-out fluid examination are higher than those of FNAC [6,7,11]. In our study, the sensitivity was higher (96.3%) than that of FNAC (76.5%); however, false positives may occur owing to peripheral blood contamination in patients with extremely high serum calcitonin [11].…”
Section: Discussioncontrasting
confidence: 49%
“…The diagnostic accuracy of MTC on FNAC ranges from 50.0% to 82.4% [4][5][6][7]. According to a meta-analysis by Trimboli et al, the detection rate of FNAC in patients with MTC ranged from 12.5% to 88.2%, with a pooled estimate of 56.4% [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The multicenter experience of the authors of the present review showed that among 34 patients with a primary MTC (i.e. thyroid nodule), 21 (62%), and 34 (100%) were identified by conventional cytology, and FNA-CT, respectively [41]. Based on these data, a cutoff of 39.6 ng/L was calculated for practice use.…”
Section: Measurement Of Calcitonin In Fna Fluids From Thyroid Nodulesmentioning
confidence: 86%
“…At cytopathologic examination the thyroid nodule appeared as benign (Thy 2). Cytologic specimens of the neck lesion had inadequate report, while thyroglobulin and calcitonin in washout fluids were undetectable and excluded metastasis from thyroid [2,3]. Thus, we decided to perform a core needle biopsy (CNB) of the neck mass.…”
Section: Case Reportmentioning
confidence: 99%